The Role Of Strategic Analysis In Managing The Crises Of The Syrian Industrial Organizations (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of  this research is to show the role of strategic analysis in  crisis management in one of the Syrian industrial organizations, which is  the  general corporate of tobacco  -coastal region branch)The research relied the analysis descriptive approach as a general method, the data was collected by way of questionnaire and personal interview       The most important results of the research have been represented as follows :There is an important role of applying the strategic analysis process in crisis management, the largest role was the process of strategic analysis of the external environment The most important recommendations the following:- The general corporate of tobacco must persevere  its way in analyzing the environment, because of its positive role in crisis management and strive to improve this process, and that the most important thing you must do is the following:-adopting  the scenario method in analyzing-analyzing its organizational culture-provision developed information systems that help its process in strategic analysis